2020
DOI: 10.1210/jendso/bvaa073
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 in African Americans and Caucasians in Relation to Lp(a) Level, Apo(a) Size and Heritability

Abstract: Abstract Context Inhibition of proprotein convertase subtilisin/kexin type 9 (PCSK9) reduces lipoprotein(a) [Lp(a)] levels, but the association of PCSK9 with Lp(a) level and its major determinant, apolipoprotein(a) [apo(a)] size, is not fully understood. Objective Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…So far, no GWAS of PCSK9 levels in African Americans has been published. Although a recently conducted study estimated the PCSK9 heritability at 47% in Europeans ( 11 ), SNPs described so far only explained 4% of the trait’s variance ( 9 ). This and the limited sample size of previous studies ( N = 1215 and N = 3290) suggest that further genetic associations could be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…So far, no GWAS of PCSK9 levels in African Americans has been published. Although a recently conducted study estimated the PCSK9 heritability at 47% in Europeans ( 11 ), SNPs described so far only explained 4% of the trait’s variance ( 9 ). This and the limited sample size of previous studies ( N = 1215 and N = 3290) suggest that further genetic associations could be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed a strong positive association between PCSK9 concentrations and future CV events in Asian patients. The frequency of PCSK9 variations and concentrations vary among different ethnic groups ( 44 , 45 ). The PCSK9 R46L and A443T variants are associated with lower LDL-C concentrations.…”
Section: Discussionmentioning
confidence: 99%